Pedagogical tools for teaching multimedia: AI, digital storytelling, and serious games - Pazmiño Palma , Edgar Fernando; Benavides Torres , Evelin Nataly; López Goyez , Juan Pablo (SATHIRI, 2025)
The research proposes pedagogical tools for teaching Multimedia in Higher Education, which promote collaborative learning, creativity and innovation. The research was developed within the framework of the International Congress of Multimedia and Audiovisual Production: Challenges and Opportunities in a Sustainable World, and compiles the research conducted by the conferences related to the integration of AI, storytelling and serious games to the process of teaching Multimedia at the Polytechnic State University of Carchi. The approach of this work was qualitative, with descriptive and documentary research. A bibliographic search was conducted in regional databases and SCOPUS, including inclusion and exclusion criteria, to determine research that present findings on didactic strategies for teaching Multimedia. The results showed that AI presents great benefits in the personalization of learning, adapting to design and creativity criteria to generate new audiovisual content, through the use of generative AI, natural language modules and intelligent tutoring systems. Digital storytelling, through such a common activity as storytelling, allows the development of different communication skills, concept apprehension, critical thinking and technological skills among students. Serious games transcend traditional education and present themselves as a creative, innovative, and, above all, engaging approach that motivates users, thus facilitating learning. It is concluded that there are limitations to the effective integration of AI, digital storytelling, and serious games, as there are insufficient regulations and policies to effectively guide teachers and students in building knowledge, prototyping, and multimedia designs using these strategies.